PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI PEGAWAI DALAM MEMBERIKAN PELAYANAN PRIMA PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN, DAN ASET DAERAH KABUPATEN SOPPENG - Heriati Heriati; ansar ansar (STIE AMKOP, 2017)
Abstract This research aims: 1) Compensation Effect partially on employee motivation; 2) Effect of Work Environment partially on employee motivation; 3) Effect of Compensation and Working Environment simultaneously towards employee motivation . The research was conducted at the Department of Revenue, Support of Finance, and Asset Soppeng Regency. The population in this study were all employees in the Department of Revenue, Support of Finance and Asset Soppeng with 142 employees. A technique of determining the number of samples in this study is based on a formula slovin thus obtained a sample of 59 employees. Analysis of the data in this study using multiple linear regression. The study concluded that: 1) Compensation partially has positive and significant impact on employee motivation; 2) The working environment is partially has positive and significant impact on employee motivation. 3) Compensation and Working Environment simultaneously have positive and significant impact on employee motivation. Keywords: Compensation, Work Environment, Motivation.